Investigating the Factors Affecting Customer-Based Brand Equity in Selected Private Hospitals in Tehran and Kerman - Mahmood Nekoei-moghadam; Anahita Behzadi; Khalil Kalavani; Zahra Naderkhah (Tehran University of Medical Sciences, 2021)
Introduction: Branding is one of the most important needs of any organization to survive and improve the quality of provided products and services. Today, branding is also being increasingly used by health organizations and has become one of the important elements for improving the quality of services provided by hospitals as the main body of health services. In the present study, the factors affecting the customer-based brand equity were investigated in selected hospitals. Materials and Methods: This is a descriptive-analytical and cross-sectional study. Using stratified random sampling method, 350 patients were selected from private hospitals in Tehran and Kerman in 2020. Data were collected through a questionnaire and the Stata software V.14 was used for data analysis. Results: The average customer-based brand equity was higher in women, those with a degree lower than diploma, and in surgical treatment group. Different dimensions of hospital brand value including perceived quality (average), patient loyalty (average), brand image (good) and service brand value (very good) were evaluated and average customer-based brand equity received 76.38 points out of 100 and was at a high level. Conclusion: Hospital brand value has an important effect on hospital marketing. Hospitals can take steps to attract and retain patients and can create a competitive advantage over others. The results showed the positive effect of perceived quality, patient loyalty, brand image and service brand value on customer-based brand equity.